Aspek Komunikasi Visual pada Ruang Hunian Vertikal di Jakarta - Atria Nuraini Fadilla (JURNAL RUPA, 2018)
The title of this research is "Social Media Strategy on Clean Air Campaign (Visual Communication Approach Strategy on Vertical Housing in Jakarta)". The methodology used in this research was by using campaign theory with focus on strategic communication approach. Data collection method is using purposive sampling technique subject for in-depth interview. Based on the in depth interview survey conducted on seven informants using purposive sampling technique, it can be concluded that there are different opinion about clean air campaign using window farming method among apartment residents and flat residents in the area of initial knowledge, source of knowledge, social media and its socialization intensity, and image / text dominance in campaign content. Keywords: Social Media, Window Farming, Campaign, Apartments, Flats